What does corpus linguistics have to offer to language assessment?. (October 2017) - Xi, Xiaoming
In recent years, continuing advances in technology have increased the capacity to automate the extraction of a range of linguistic features of texts and thus have provided the impetus for the substantial growth of corpus linguistics. While corpus linguistic tools and methods have been used extensively in second language learning research, they have also been used increasingly in the design and validation of language assessments (Callies & Götz, 2015; Deshors, Götz, & Laporte, 2016; Park, 2014). The collection of papers in this special issue represents an intentional and systematic effort to encourage the cross-pollination of corpus linguistics and language assessment. The research foci of these papers take this cross-disciplinary area in exciting, new directions. At the same time, the papers also point to some important gaps and provide inspiration for additional research. In this commentary, I offer some perspectives on how the papers contribute to this cross-disciplinary research area and then share my reflections on some of the gaps that need to be narrowed or closed if language testing researchers and practitioners are to take full advantage of the potential of corpus linguistics for language assessment.